PSICOPEDAGOGÍA Y SU IMPACTO EN EL RENDIMIENTO ACADÉMICO DE LOS ESTUDIANTES DEL 5TO AÑO DE EGB DE LA PARROQUIA CAMILO PONCE, DEL CANTÓN BABAHOYO- PERIODO LECTIVO 2024-2025. - DELGADO BENAVIDES GABRIELA BRIGETTE (2024)
This research work investigates the relationship between psychology and pedagogy, which unites psych pedagogy, given that this is a discipline that studies people and their behaviors in the teaching-learning process of basic general education students. The purpose of this research is to identify the impact that psych pedagogy produces on academic performance, due to emotional lows such as; Stress, anxiety, demotivation, low self-esteem, lack of parental attention are factors that negatively affect and are reflected in the performance of the students of the 5th year of Basic General Education of the Camilo Ponce Parish, belonging to the province of Los Ríos- cantón Babahoyo, it should be emphasized that this affects both the school environment and the social environment. Through surveys conducted with students, in the development of this research, the background of psych pedagogy and its impact on academic performance are revealed. Through this research we hope to contribute positively, facilitating understanding and improvement in the teaching and learning processes, taking into account the specific educational needs that each of the students presents.